(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This article discusses the advantages and problems of creating family courts in the Republic of Uzbekistan. The author puts forward a number of advantages of creating family courts with a detailed, empirical and comparative analysis. At the same time, potential disadvantages and some problems are carefully analyzed. The author analyzed the experience of such foreign countries as the USA, Japan, Kazakhstan, Germany, etc. The article provides substantiated conclusions that support the creation of family courts in the Republic of Uzbekistan